Women’s ventures in a rural context: Livelihood and identity - Carbó, Mònica; Baylina, Mireia; Garcia-Ramon, Maria Dolors (Hagar: Studies in Society and Culture, 2013)
The Spanish rural area continues to undergo a process of transformation that lias impacted society and space in an unequal way. The process of dismantling agriculture, together with demographic loss, have pushed rural society to seek alternatives so as to adapt to an economic model in crisis. In the south of Catalunya (Catalonia), the county of Terra Alta is an isolated region of strong agricultural tradition and weak industrialization, with the lowest regional rate of female employment. In this context, women of various ages have initiated business ventures in the area that have shown signs of economic vitality. Among their motivations is the need for employment, along with symbolic and ideological elements that reinforce the rural identity and are crucial for women’s attachment to place. However, the success of their activity is highly influenced by their gender identity. The paper presents the experiences of women entrepreneurs in a rural context of a strong patriarchal character, showing how women’s paid activity depends not only on the offer of employment or the possibility of businesses, but also on how women imagine themselves and on the social acceptance that their images generate.